Determination of the diameter of columnar jointed volcanics using bifurcation analysis. Issue 1 (15th March 2018) - Anderssohn, Robert; Hofmann, Martin
Abstract: The development of the typical hexagonal pattern of solidifying volcanic material can be described by fracture mechanics. While following the moving inhomogeneous temperature field, these columns reach a steady growth with a certain diameter. This spacing increases sometimes instantaneously. Using a bifurcation analysis based on the free Helmholtz energy this phenomenon is investigated and presented with this contribution. In order to handle the complex three‐dimensional geometry, regularity in the pattern and a Fourier series expansion of the crack contour are used. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)